(untitled) (Bangladesh Journal of Agricultural Research, 2012)
Field experiment was conducted to compare and investigate the concentration levels of heavy metals in leafy vegetables with growth stage and plant species variations on an experimental field near the net house of Soil Science Division, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur, Bangladesh during November 2008 to January 2009. Seeds of spinach (Spinacia oleracea), red amaranth (Amaranthus tricolor) and amaranth (Amaranthus oleraseus) were sown on 14 November 2008. Plant and soil samples were collected at different growth stages, such as at 20, 30, 40, and 50 days after sowing (DAS). The concentrations of lead (Pb), cadmium (Cd), nickel (Ni), cobalt (Co), and chromium (Cr) in plant increased with the age of the plant, but the increase was not linear. The rate of increase of concentration of these metals at 20 to 30 DAS was found lower than that at 30 to 40 DAS, except Cr. Heavy metal content gradually increased at the early growing stage and fall during later stages of growth. The significant differences (P < 0.01) were observed between the mean metal concentrations in the three vegetables species. The Pb and Co concentrations in amaranth were found higher compared to those found in spinach and red amaranth. Spinach exhibited higher levels of Cd and Cr than those of other vegetables. However, the three vegetables did not differ significantly in its Ni concentration. The order of heavy metal level in different vegetables was Cd<Co<Pb<Ni<Cr. In vegetable species in respect of heavy metal concentration Cd, Ni, and Cr was highest in spinach and amaranth showed highest concentration in Pb and Co. The highest correlation between soil-plant was found for Cd, while the lowest for Ni. Metal concentrations in the vegetables studied were found lower than the maximum allowable level in India but the concentrations of Cd and Cr were higher than the allowable levels set by the World Health Organization (WHO). DOI: http://dx.doi.org/10.3329/bjar.v36i4.11743 Bangladesh J. Agril. Res. 36(4): 563-574, December 2011